Modern tendencies of functioning of nongovernmental pension funds in the system of obligatory pension insurance - Gulnara Fatkhlislamova (Управление)
This article summarizes and systematizes key trends in the development of non-state pension funds (NPFs) in the exercise of the functions of trust management of pension savings of citizens for the period from 2005 to 2017. The participation of non-state pension funds in the compulsory pension insurance system has led to their emergence as the largest insurer, so starting from 2016, the NPF, as a large institutional investor, began to concentrate more than half of all pension savings funds transferred to management. A quantitative analysis of the institutional structure of the Russian system of trust management of the pension system means allows determining the main directions of its transformation; there is a clear tendency to a reduction: the total number of NPFs operating in the OPS system. The article defines the strategy of investing APFs in various classes of assets during the study period, it has been revealed that of the total amount of invested pension savings in corporate securities, 2/3 of them fall on NPF investments. Over the last analyzed period, there has been a sharp increase in the investment of pension savings of NPFs in government securities, which is largely due to the tightening of regulatory requirements for the risk level of portfolio investment. Important areas of research are evaluating the effectiveness of the functioning of APFs in the system of compulsory pension insurance from the position of comparing the accumulated return on the NPF portfolio with accumulated inflation for the period analyzed, and also according to the criterion of actually accumulated investment income with indexed income on inflation.